Revista de Literatura: tomo 9 (1956), tomo [10] (1956), tomo 11 (1957), tomo 12 (1957). - A., T. (El Colegio de México, 1971)
Se reseñó: Revista de literatura: tomo 9 (1956), tomo [10] (1956), tomo 11 (1957), tomo 12 (1957).